2011
DOI: 10.1016/j.nima.2011.06.006
|View full text |Cite
|
Sign up to set email alerts
|

Negative ion drift velocity and longitudinal diffusion in mixtures of carbon disulfide and methane

Abstract: Negative ion drift velocity and longitudinal diffusion has been measured for gas mixtures of carbon disulfide (CS2) and methane (CH4)' Measurements were made as a function of total pressure, CS 2 partial pressure and electric field. Constant mobility and thermal-limit longitudinal diffusion is observed for all gas mixtures tested. Gas gain for some of the mixtures is also included.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
9
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(9 citation statements)
references
References 16 publications
0
9
0
Order By: Relevance
“…The choice of the target medium is thus critical. CS 2 offers the possibility to drift negative ions, which enables very long drift distances with minimal diffusion and hence large volumes [51][52][53][54][55][56][57]. Directional electron-drift TPCs are using CF 4 , for the spin content of 19 F that enables a sensitivity to spin dependent interaction [58], and for the properties of this gas: electron drift velocity, diffusion and its scintillation output, which can be used for optical readout [22,59].…”
Section: B Track Reconstructionmentioning
confidence: 99%
See 1 more Smart Citation
“…The choice of the target medium is thus critical. CS 2 offers the possibility to drift negative ions, which enables very long drift distances with minimal diffusion and hence large volumes [51][52][53][54][55][56][57]. Directional electron-drift TPCs are using CF 4 , for the spin content of 19 F that enables a sensitivity to spin dependent interaction [58], and for the properties of this gas: electron drift velocity, diffusion and its scintillation output, which can be used for optical readout [22,59].…”
Section: B Track Reconstructionmentioning
confidence: 99%
“…The key feature of the DRIFT detector is the fact that negative ions (CS − 2 ) are used to transport the ionization signal to the readout plane composed of Multi-Wire Proportional Counters (MWPC) [57]. It opens the possibility to develop TPCs with very long drift distances with minimal diffusion and hence large volumes [53][54][55][56][57]. The gas mixture currently used is 73% CS 2 + 25% CF 4 + 2% O 2 at a pressure of 55 mbar.…”
Section: Driftmentioning
confidence: 99%
“…Ideally, in a negative ion TPC (NITPC), electrons would be rapidly captured by molecules with moderate electron affinity at the site of ionization, transported with minimum diffusion in 3 dimensions to the readout plane where they would be stripped and then undergo normal electron avalanche to produce gas gain at the readout plane. A number of authors have found molecules approaching this ideal 1,3,4,5,6 . For the past decade the Directional Recoil Identification From Tracks (DRIFT) collaboration 7 has utilized carbon disulfide, CS 2 , for negative ion transport in a low pressure NITPC to search for dark matter.…”
Section: Introductionmentioning
confidence: 98%
“…The choice of the target medium is thus critical. CS 2 offers the possibility to drift negative ions, which enables very long drift distances with minimal diffusion and hence large volumes [51][52][53][54][55][56][57]. Directional electron-drift TPCs are using CF 4 , for the spin content of 19 F that enables a sensitivity to spin dependent interaction [58], and for the properties of this gas: electron drift velocity, diffusion and its scintillation output, which can be used for optical readout [22,59].…”
Section: B Track Reconstructionmentioning
confidence: 99%
“…The key feature of the DRIFT detector is the fact that negative ions (CS − 2 ) are used to transport the ionization signal to the readout plane composed of Multi-Wire Proportional Counters (MWPC) [57]. It opens the possibility to develop TPCs with very long drift distances with minimal diffusion and hence large volumes [53][54][55][56][57]. The gas mixture currently used is 73% CS 2 + 25% CF 4 + 2% O 2 at a pressure of 55 mbar.…”
Section: Driftmentioning
confidence: 99%